MECHANICAL ANALYSIS AND DESIGN FOR PHOTO-ELECTRICITY MEASUREE QUIPMENT SHAFTING IN MOBILE-PLATFORM - JIANG WeiWei; HU HongYi; LIU RuZhen; HE Bi; CHEN ZHiMing (Jixie qiangdu)
Design the shafting for photoelectric-equipment used in mobile-platform,mobile-platform. First,based on structure and assemble technicalof bearing put forward three kinds of structure for shafting,then,deduce the revise formulation for shafting aim at vibratory environment of mobile-platform,which was the theory basis for the shafting design in mobileplatform photo-electricity equipment.